A new method to integrate ZnO nano-tetrapods on MEMS micro-hotplates for large scale gas sensor production. (17th August 2016) - Marasso, S L; Tommasi, A; Perrone, D; Cocuzza, M; Mosca, R; Villani, M; Zappettini, A; Calestani, D
Abstract: A new method, which is easily scalable to large scale production, has been developed to obtain gas sensor devices based on zinc oxide (ZnO) nanostructures with a 'tetrapod' shape. The method can be easily extended to other kinds of nanostructures and is based on the deposition of ZnO nanostructures through polymeric masks by centrifugation, directly onto properly designed MEMS micro-hotplates. The micromachined devices, after the mask is peeled off, are ready for electrical bonding and sensing test. Sensor response has been successfully measured for some gases and volatile organic compounds with different chemical properties (ethanol, methane, nitrogen dioxide, hydrogen sulfide).